Chaihu-Shugan-San ameliorates tumor growth in prostate cancer promoted by depression via modulating sphingolipid and glycerinphospholipid metabolism - Li, Wei; Zhou, Runze; Zheng, Jie; Sun, Bo; Jin, Xin; Hong, Min; Chen, Ruini (Frontiers in Pharmacology, 2022)
Background: Psychologic depression is a pivotal pathological characteristic and has been shown to promote prostate cancer (PCa) progression. Chaihu-Shugan-San (CSS), a well-known Chinese herbal decoction, exhibits efficacy in the treatment of stress-accelerated PCa. However, the underlying mechanism of CSS on resisting PCa growth is still unknown and further study is needed. Objective: To evaluate the effects of CSS on stress-accelerated PCa in a BALB/C nude mice model and to investigate the underlying mechanisms. Methods: PC-3 cells were implanted into BALB/C nude mice, and the stressed mice were exposed to chronic unpredictable mild stress (CUMS) to study the effects of CSS. Analyses of PCa growth were evaluated by tumor volume and tumor weight. Analyses of depression-like behaviors were evaluated by sucrose consumption test, tail suspension test and open field test. Network pharmacology was used to analyze the potential targets and signaling pathways of CSS against PCa. untargeted lipidomics were used to analyze the serum lipid profiles and further elucidate the possible mechanism. Results: In the CUMS stressed PCa mice, CSS can restrain tumor growth with reduced tumor volume and tumor weight and depression-like behaviors with increased sucrose consumption, reduced immobility duration and increased total distance and center distance. Network pharmacology suggested the lipid metabolism related pathways is the most likely potential targets of CSS against PCa. Using untargeted lipidomics analysis, Significant changes in the level of 62 lipids were observed in PCa bearing mice under CUMS treatment. The levels of glycerophospholipids including phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI) and phosphatidylglycerol (PG), except PC (18:0_22:6) and PC (18:0_20:4), were significantly increased. Likewise, the levels of all sphingolipids (including sphingomyelin (SM), ceramides (Cer) and hexosyl-1-ceramide (Hex1Cer)) and diglyceride (DG) (32:1e) were significantly increased. CSS water extract was found to contribute restore 32 lipids including 6 sphingolipids, 25 glycerophospholipids and 1 glyceride. Conclusions: This study is the first to delineate the lipid profile of stressed PCa BALB/C nude mice using untargeted lipidomics analysis. CSS restrained tumor growth and ameliorated depression-like behaviors by reprogramming lipid metabolism. Intervening lipid metabolism could be a preventive and therapeutic approach for PCa patients with depression.